Organizational resources, KM process capability and strategic flexibility: a dynamic resource-capability perspective. Issue 7 (15th May 2018) - Bamel, Umesh Kumar; Bamel, Nisha
Abstract : Purpose: Strategic flexibility is largely considered a source of competitive advantage, yet strategic flexibility in relation to organizational resources and knowledge management (KM) process capability is not well studied. To address this gap, this study aims to assesses the relationship of organizational resources (technical and social resources) and strategic flexibility through KM process capability. Design/methodology/approach: This paper is built on the assumptions of the resource-based view and the dynamic capability perspective of firm. Two types of organizational resources – technical and social – were identified from relevant literature. Data were collected from 23 small- and medium-sized firms (family owned firms) using a 37-item questionnaire. In addition to descriptive statistics, multiple hierarchical regressions and bootstrapping were used to test the study hypotheses. Findings: Findings suggest that organizational resources are positively and significantly related with strategic flexibility, and KM process capability partially mediates these relationships. Research limitations/implications: The paper adds to strategic flexibility literature by exploring and assessing the linkage of organizational resources with strategic flexibility through KM process capability. Originality/value: Findings of this research may help organizations and practitioners in enhancing strategic flexibility of firm.